Growth of cocoa seedlings (Theobroma cacao L.) in application of cow manure compost and density of Bacillus subtilis bacteria - Kasim, Nurlina; Nasaruddin; Widiayani, Nuniek; Andi Syaiful, Syatrianti; Ningsih, Sry Rahayu (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
Cocoa rejuvenation is important to maintain high productivity. The rejuvenation mainly uses seedlings; thus providing high-quality seedlings is important. This research aimed to determine the effect of various doses of cow manure compost and the density of Bacillus subtilis bacteria on the growth of cocoa seedlings. The research was implemented at the Teaching Farm, Faculty of Agriculture, Hasanuddin University, Makassar City, from 2021 to 2022. The experiment was arranged in a split-plot design with three replications. The main plot was the dose of cow manure (without compost, 1.25 kg per polybag, and 2.5 kg per polybag). The subplot was the density of Bacillus subtilis (without bacteria, 104 CFU.mL-1, 108 CFU.mL-1, and 1012 CFU.mL-1). The results showed an interaction between the dose of cow manure 2.5 kg per polybag and the bacterial density 1012 CFU.mL-1 on chlorophyll a (347.91 mol.m-2), chlorophyll b (158.33 mol.m-2), total chlorophyll (444.57 mol.m-2), and leaf area of cocoa seedlings (813.96 cm2). A compost dose of 2.5 kg per polybag showed the best results for plant height (8.98 cm). Keywords: bacteria density; bivariate correlation; chlorophyll content; manure dose; organic fertilizer